2003
DOI: 10.1007/s00198-003-1455-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sub-elite competitive running on bone density, body composition and sexual maturity of adolescent females

Abstract: The attainment of optimal peak bone mass during adolescence is important in the primary prevention of osteoporosis. Exercise may contribute to skeletal development and bone density during growth, although competitive exercise is suggested to have an adverse effect. This study assesses the effect of moderate exercise on the bone density of adolescent females. Additionally, other factors which significantly influence attainment of peak bone mass were identified. This was a cross-sectional study of 42 adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
0
9
2
3
Order By: Relevance
“…(39)(40)(41)(42) A previous study by Lucas and colleagues that compared adolescent runners and nonrunners found no differences between runners (n ¼ 15) and nonrunners (n ¼ 27) in body weight or BMD at each bone site, and it therefore was concluded that runners' exercise activity did not negatively affect their bone mass. (43) Although the results of that study might appear contradictory to our findings, the runners in that study sample ranged in age from 12 to 14 years. (43) Since the bone-mass differences between runners and nonrunners in the current sample became recognizable after age 14 years, our findings do not contrast with the results from Lucas and colleagues (43) ; instead, they may provide an expanded understanding of the effect of prolonged exposure to endurance running on adolescent bone mass.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…(39)(40)(41)(42) A previous study by Lucas and colleagues that compared adolescent runners and nonrunners found no differences between runners (n ¼ 15) and nonrunners (n ¼ 27) in body weight or BMD at each bone site, and it therefore was concluded that runners' exercise activity did not negatively affect their bone mass. (43) Although the results of that study might appear contradictory to our findings, the runners in that study sample ranged in age from 12 to 14 years. (43) Since the bone-mass differences between runners and nonrunners in the current sample became recognizable after age 14 years, our findings do not contrast with the results from Lucas and colleagues (43) ; instead, they may provide an expanded understanding of the effect of prolonged exposure to endurance running on adolescent bone mass.…”
Section: Discussioncontrasting
confidence: 85%
“…(43) Although the results of that study might appear contradictory to our findings, the runners in that study sample ranged in age from 12 to 14 years. (43) Since the bone-mass differences between runners and nonrunners in the current sample became recognizable after age 14 years, our findings do not contrast with the results from Lucas and colleagues (43) ; instead, they may provide an expanded understanding of the effect of prolonged exposure to endurance running on adolescent bone mass. The primary limitation of this study is its cross-sectional design.…”
Section: Discussioncontrasting
confidence: 85%
“…This finding suggests that intensive sports training before menarche delays menarche. The possible reasons for this late onset of menarche may include the small amount of fat tissue, as well as the physical and mental stress to which athletes are exposed [3,[13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…42 On the other hand, in sub-elite, moderately exercising female runners, no effect on pubertal development was demonstrated. 43 Dance training has been shown to be associated with a high incidence of menstrual dysfunction, particularly in disciplines such as ballet. 35 Ballet dancers begin strenuous training at an early age while undergoing intensive exercise and heavy caloric restrictions (this leading to energy deficit) in order to perform at a competitive level and retain a lean physique.…”
Section: Menstrual Disorders In Specific Sportsmentioning
confidence: 99%